THE LAW AS VALUE - Baikovs, Aleksandrs (Administrative and Criminal Justice, 2019)
The paper deals with the category of “values”, the right as a value, and fundamental values of law; including freedom, justice, and equality are analyzed.The relevance of the research is determined not only by the apparent lack of exploration of the problem but also by the fact that the value of right and legal values determine direction and meaning, as well as the content of the rules of law, which is their normative expression, and, ultimately, appearing as a kind of basis for the legal culture, the source of the legal consciousness’s formation and establishing a legal order, ensuring the efficiency of legal regulations due to the using the embodiment in reality of freedom, justice, equality.Legal norms themselves acquire the importance of values and become the subject of evaluation. Among values themselves, which act as an ideal justification of the rules of law, the rules of law themselves and assessments, on the one hand, there are not only close ties but also mutual transitions. Therefore, both their interrelated explanations and differentiation are necessary.In this regard, the role and importance of rights and of the abovestated legal values, including the historically-legal aspect, their historical conditionality are disclosed, the semantic content and the importance in the establishment of the legitimacy regime are analyzed, the points of view expressed in the  research literature on the nature of legal values, signs, hierarchy,  the role in social and normative regulation are considered, the difference between value and the object of value or good is emphasized.